7 - Globalization, the Bologna Process and African Universities: Limits and Contradictions of Market-oriented Higher Education Reforms - Isaac N. Obasi,; Akinpelu O. Olutayo, (Journal of Higher Education in Africa, 2009)
One of the greatest challenges posed by neo-liberal capitalist globalization is com- petitiveness. The birth of the Bologna Process in 1999 and the launching of the Erasmus Mundus in 2004 were serious attempts by Europe to make its higher education one of the most competitive systems in the world. Both initiatives were aimed at enhancing the compatibility and comparability of European higher education among its members as well as its attractiveness to other regions of the world. The implementation of the Bologna Process has, however, exposed the limits and contradictions of market-oriented higher education reforms. The experience of Europe has shown that neo-liberal higher education reforms under globalization can be manipulated as dictated by the exigencies of national interests. Europe has declared higher education a public good to be made equally accessible to all and to remain a public responsibility. This paper contends that Africa has a lot to learn from the implementation of the Bologna Process. Furthermore, the paper raises policy concerns about the implications of the implementation of the Erasmus Mundus so far from 2004 to 2008, as some evidence suggests that the students benefiting from the Erasmus Mundus programme may end up being part of the brain drain rather than brain gain for Africa. This would therefore hinder rather than promote African development, which the programme ostensibly aims at achieving. Consequently, the paper recommends that policy-makers in Africa should be weary of attempts to use the Bologna Process and the Erasmus Mundus programme as a subtle and new launching pad promoting the brain drain in Africa. The paper also calls on Africa political leaders to uphold the Accra Declaration on GATS and the Internationalization of Higher Education in Africa (2004), a policy that would greatly help to check the excesses of neo-liberal higher education reforms under globalization.